Improving Teaching "Nuclear Energy" on the Example of Nuclear Fuel Cycles in Universities - A. Kh. Ramazanov; E.Kh. Bozorov (Genius Journals, 2023)
This article analyzes and discusses the technical features of nuclear fuel cycles in specialized universities. The nuclear fuel cycle is a set of methods for the extraction and production of fuel for nuclear reactors, its preparation for use and disposal. The term "fuel cycle" refers to the fact that spent or irradiated nuclear fuel (SNF), after special processing, can be reused. To date, the key problem of nuclear non-proliferation is a fairly simple transition from the peaceful use of atomic energy to the military.
Keywords: problem; technical features; nuclear fuel cycle; nuclear fuel